Heritage Tourism in Iran - Roque, Maria Isabel (2019)
Iranian history, with roots in the oldest civilizations in western Asia, has provided significant heritage, both tangible and intangible, allowing the country to be considered as a major cultural tourism destination for both nationals and foreigners. The focus on Iranian history and heritage aims to confirm the country’s potential for attracting international tourists, while a negative image prevails abroad of a radical theocratic regime with a hostile internal political environment, alongside the instable geopolitical situation of the region. However, the changing political situation, now more secure and safe, allows an attempt to remove these prejudices, which may be achieved through the promotion of heritage and cultural tourism.